NORTRIPTYLINE VERSUS SUSTAINED-RELEASE MORPHINE VERSUS COMBINATION THERAPY IN CHRONIC LUMBAR RADICULOPATHY A RANDOMIZED CROSSOVER TRIAL (Cuestiones de Fisioterapia, 2019)
diabetic neuropathy and postherpetic neuralgia, and little evidence is given on lumbar radiculopathy. Purpose: To evaluate the analgesic efficacy of nortriptyline, sustained-release morphine, a combination of the two, and placebo on patients with chronic lumbar radicular pain. Methods: A randomized, four-period, double-blind, crossover trial was done on 121 patients with chronic lumbar radiculopathy where sustained-release morphine, nortriptyline, combination therapy, and placebo were used. An outcome measure of average leg pain was the primary, and secondary measures were global pain, disability, mood, and quality of life. Findings: Nortriptyline showed a significant reduction in average and worst pain score by a ratio of about 2533 percent over placebo without zero confidence intervals. Morphine had small, not significant pain reliefs. Combination therapy produced comparable analgesic effects to nortriptyline monotherapy, and an extra effect in mood and quality of life. Conclusion: Nortriptyline and morphine alone or combined with morphine were better than morphine monotherapy and placebo in reduction of pain and functional results of chronic lumbar radiculopathy.